2010
DOI: 10.1007/s10787-010-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Antihypercholesterolaemic effect of ginger rhizome (Zingiber officinale) in rats

Abstract: The results revealed that the hypercholesterolaemic rats treated with aqueous ginger infusion in the three doses used after 2 and 4 weeks of treatment induce significant decrease in all lipid profile parameters which were measured and improved the risk ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 23 publications
(24 reference statements)
13
33
0
1
Order By: Relevance
“…33 Mozaffari et al observed that daily intake of three grams of ginger for eight weeks in diabetic patient leads to a reduction in serum LDL-C level, but does not affect the levels of total cholesterol, TG and HDL-C. 24 The finding of the present study on the effect of ginger on serum cholesterol concentration is consistent with the results of many animal studies. 28,34 The reduction of cholesterol by ginger can be explained as follows: Ginger can induce cholesterol conversion to bile acids by increasing activity the cholesterol-7 -α-hydroxylase enzyme and ultimately lead to, decline serum cholesterol level. 33 Also, it has been reported that ginger compounds suppress the synthesis of cholesterol in the mice liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…33 Mozaffari et al observed that daily intake of three grams of ginger for eight weeks in diabetic patient leads to a reduction in serum LDL-C level, but does not affect the levels of total cholesterol, TG and HDL-C. 24 The finding of the present study on the effect of ginger on serum cholesterol concentration is consistent with the results of many animal studies. 28,34 The reduction of cholesterol by ginger can be explained as follows: Ginger can induce cholesterol conversion to bile acids by increasing activity the cholesterol-7 -α-hydroxylase enzyme and ultimately lead to, decline serum cholesterol level. 33 Also, it has been reported that ginger compounds suppress the synthesis of cholesterol in the mice liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gujral et al 1978 Ginger (aqueous extract) Decreased LDL-cholesterol, serum total cholesterol, and triacylglycerol. El-Rokh et al 2010 Ginger (gingerol) Prevented high fat diet-induced hyper-lipidemia by cholesterol metabolism. Naidu et al 2016 Coriander (seed oil) Had hypocholesterolemic activities in rats fed a cholesterol-rich diet.…”
Section: Gingermentioning
confidence: 99%
“…Many other medicinal plants showed hypocholesterolemic activity, such as leaf extracts of lupeol and lupeol linoleate [119], Averrhoa bilimbi fruit [120], Cistanche tubulosa extract [121], spirulina [122], peanuts [123], Cnidoscolus chayamansa [124], aqueous ginger (Zingiber officinale) [125], Citrus bergamia Risso and Poiteau juice [126], Momordica charantia fruit [127], cocoa products [128], garlic [129], aç a ı (Euterpe oleracea Mart.) [130], citrus peel [131], Lycium ruthenicum anthocyanins [132], arti choke leaf extract [133], Ficus microcarpa (L.) [134], grape juice [135], Ficus racemosa [136], and Hibiscus sabadariffa extract [137].…”
Section: Miscellaneous Medicinal Plantsmentioning
confidence: 99%